Drug interaction at hERG channel: In vitro assessment of the electrophysiological consequences of drug combinations and comparison against theoretical models. Issue 4 (16th November 2017) - Wiśniowska, Barbara; Lisowski, Bartosz; Kulig, Magdalena; Polak, Sebastian
Abstract: Drugs carry a proarrhythmic risk, which gets even greater when they are used in combination. In vitro assessment of the proarrhythmic potential of drugs is limited to one compound and thus neglects the potential of drug–drug interactions, including those involving active metabolites. Here we present the results of an in vitro study of potential drug–drug interactions at the level of the hERG channel for the combination of up to three compounds: loratadine, desloratadine and ketoconazole. Experiments were performed at room temperature on an automated patch‐clamp device CytoPatch 2, with the use of heterogeneously, stably transfected HEK cells. Single drugs, pairs and triplets were used. The results provided as the inhibition of the I Kr current for pairs were compared against the calculated theoretical interaction. Models applied to calculate the combined effect of inhibitory actions of simultaneously given drugs include: (1) simple additive model with a maximal inhibition limit of 1 (all channels blocked in 100%); (2) Bliss independence; and (3) Loewe additivity. The observed IC50 values for loratadine, desloratadine and ketoconazole were 5.15, 1.95 and 0.74 μm respectively. For the combination of drugs tested in pairs, the effect was concentration dependent. In lower concentrations, the synergistic effect was observed, while for the highest tested concentrations it was subadditive. To triple the effect, it was subadditive regardless of concentrations. The square root of sum of squares of differences between the observed and predicted total inhibition was calculated to assess the theoretical interaction models. For most of the drugs, the allotopic model offered the best fit. Abstract : The study presents results of an in vitro study of potential DDIs at the hERG channel level for the combination of up to three compounds (loratadine, desloratadine, ketoconazole). The inhibition of IKr current by single compounds, pairs and triplet was assessed with use of automated patch‐clamp and stably transfected HEK cells. In lower concentrations synergistic effect was observed, while for the highest tested concentrations the total inhibition was subadditive. For triplet the effect was subadditive regardless of concentrations.